2018
DOI: 10.1002/ccd.27591
|View full text |Cite
|
Sign up to set email alerts
|

Serial intravascular ultrasound evaluation of the DESolve™ novolimus‐eluting bioresorbable coronary scaffold system

Abstract: IVUS serial evaluation of the novel DESolve BRS showed an increase in the device dimensions between baseline and 6 months, with concomitant enlargement of lumen dimensions and effective suppression of neointimal proliferation. At 18 months, no footprint of the scaffold was detected and the initial lumen enlargement was sustained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The DESolve Nx clinical study involving 126 patients showed a high device and procedural success and low rates of adverse events, including low device thrombosis (0.8%), through 24 months [51]. Serial intravascular ultrasound evaluation showed an increase in the device and lumen dimensions between baseline and six months, with no detectable footprints of the scaffold at 18 months [52]. Furthermore, in the DESolve PMCF study involving 102 patients with CAD, a low rate of TVF (3.0%) and device thrombosis (1.0%) was observed at 12 months [53].…”
Section: Desolve Bioresorbable Scaffoldmentioning
confidence: 97%
“…The DESolve Nx clinical study involving 126 patients showed a high device and procedural success and low rates of adverse events, including low device thrombosis (0.8%), through 24 months [51]. Serial intravascular ultrasound evaluation showed an increase in the device and lumen dimensions between baseline and six months, with no detectable footprints of the scaffold at 18 months [52]. Furthermore, in the DESolve PMCF study involving 102 patients with CAD, a low rate of TVF (3.0%) and device thrombosis (1.0%) was observed at 12 months [53].…”
Section: Desolve Bioresorbable Scaffoldmentioning
confidence: 97%
“…However, the propensity matched analysis demonstrated no difference in clinic performance of ®DESolve compared to ®Absorb BVS at 1 year [19]. Serial intravascular ultrasound (IVUS) has revealed an increase in the device and lumen dimensions between baseline and 6 months, with no detectable footprints of the scaffold at 18 months [20]. At 5-year clinical and imaging follow-up of the DESolve Nx clinical study [21] no definite scaffold thrombosis was reported but cardiac deaths were 2.5% and TLR rate was 4.1% (Table 2).…”
Section: Desolvementioning
confidence: 98%